P37 Hypermobile ehlers-danlos syndrome explosion in the UK!!. (June 2019) - Jenabi, Fatemeh; Leahy, Alice; Foulds, Nicola; Graaf, Hans de
Abstract : Background: Ehlers-Danlos Syndrome (EDS) is a heterogeneous group of collagen disorders. There is controversy regarding clinical diagnosis of hypermobility EDS. The Beighton score and the recent international classification of EDS are not validated in children. Clinicians get the impression that there is a substantial increase in frequency of referrals with ?EDS especially for musculoskeletal pain. Methods: In this retrospective cohort study we searched local databases of paediatric rheumatology and genetics department for referrals to the paediatric rheumatologist due to concerns regarding having hypermobile EDS. All clinic letters were carefully examined and data collected for patients age, gender, reasons for referral, diagnosis made by rheumatologist and the management plan. We did a descriptive analysis using population proportion confidence interval. Results: In the paediatric rheumatology department we identified 53 referrals (34 female), median age 11 years (range 9 months – 17 years) from June 2017 to June 2018. 59% had anxious parents with one or multiple psychosocial issues as well experiencing musculoskeletal pain. 12 patients had a family history of hypermobile EDS, three patients were diagnosed with hypermobile EDS in a private clinic, for three patients the GP had suggested EDS, one patient had possible skin features of EDS, parents of two patients had concerns following surfing the internet and one patient had a cardiac and vascular problem possibly related to EDS. The patients were diagnosed being a healthy child (49%), or having hypermobility (28%), arthralgia (8%), mechanical pain (7%), chronic pain (6%) and classical EDS (2%). Management included reassurance and discharge (21%), referral to physiotherapy (76%), referral to psychology (13%), referral to other medical teams (21%). Of all patients 11% were followed up after the initial review. The genetic department had total of 245 referrals From January 2017 to June 2018. The referral included 62 patients with ?EDS (19 paediatrics, 43 adults), 14 with ?hypermobility (12 paediatrics, two adults) and 169 hypermobile patients with ?Marfan syndrome (44 paediatrics, 125 adults). Most referrals did not have a significant family history or clinical features. Conclusion: Particular attention should be devoted to education and information in first line health care as well as to more effective management of musculoskeletal pain and parental anxiety.